Construction of Pancasila Student Mentality through Animation as Student Learning at SMKN 11 Malang - Wardhani, Fitria Maudy; Iriaji, Iriaji; Ratnawati, Ike (Fakultas Bahasa dan Seni UNP, 2024)
This research aims to determine the meaning semiotic animation